Sistem Informasi Geografis Analisis Perbandingan Kejadian Kejahatan dan Persebaran Pos Kamling Kecamatan Brebes Tahun 2023 - Kresna, Ande; Herlambang, B.A.; Anam, A.Khoirul (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
Environmental security is an important aspect in maintaining public order, particularly in areas with high social activity. This study aims to analyze the spatial relationship between the distribution of Neighborhood Security Posts (Pos Kamling) and crime levels in Brebes Subdistrict in 2023 using a Geographic Information System (GIS). The data used in this study are secondary data in the form of the number of Pos Kamling and records of resolved crime cases, obtained from the Brebes Sector Police and the Brebes Regency Central Bureau of Statistics. The research method employed is descriptive spatial analysis using an overlay technique of administrative boundary maps with QGIS software. The results show that out of 23 villages/urban villages in Brebes Subdistrict, 11 areas are categorized as safe due to the absence of reported crime cases. Brebes Urban Village and Pasarbatang recorded the highest crime rates, with 5 and 4 resolved crime cases respectively, despite having a relatively high number of Pos Kamling. These findings indicate that the high number of Pos Kamling in urban areas is a response to higher security vulnerability rather than solely an indicator of low crime levels. The application of GIS in this study provides informative spatial visualization that can serve as a basis for evaluation and policy formulation in environmental security management at the subdistrict level.